2013
DOI: 10.1016/j.jcmg.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Arterial Activity on Routine FDG PET/CT Images Improves Prediction of Risk of Future CV Events

Abstract: Arterial FDG uptake, measured from routinely obtained PET/CT images, substantially improved incident CVD prediction beyond FRS among individuals undergoing cancer surveillance and provided information on the potential timing of such events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
232
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 292 publications
(250 citation statements)
references
References 37 publications
7
232
1
3
Order By: Relevance
“…31,32 In addition, higher arterial FDG uptake is associated with a substantially increased risk for subsequent stroke and MI. [33][34][35] Taken together, these studies provide justification for using arterial FDG-PET/CT imaging to provide a meaningful measure of arterial inflammation in human clinical studies.…”
Section: See Related Article Pp 372-380mentioning
confidence: 85%
“…31,32 In addition, higher arterial FDG uptake is associated with a substantially increased risk for subsequent stroke and MI. [33][34][35] Taken together, these studies provide justification for using arterial FDG-PET/CT imaging to provide a meaningful measure of arterial inflammation in human clinical studies.…”
Section: See Related Article Pp 372-380mentioning
confidence: 85%
“…Data from the prospective Dublin Carotid Atherosclerosis Stroke Study showed that increased carotid artery 18 F-FDG uptake can identify patients with increased risk of early stroke recurrence, independent of age and stenosis severity (Figure 4a,b) [122]. Moreover, a retrospective study of imaging from 513 cancer-free patients examined over a 4-year period found that aortic 18 F-FDG uptake strongly predicted risk of cardiovascular events independent of traditional risk factors (hazard ratio: 4.71, P < 0.001), with nearly 30% net reclassification improvement over Framingham risk score in the highest risk group [123].…”
Section: Positron Emission Tomographymentioning
confidence: 96%
“…Furthermore, 18 F‐FDG PET/CT can provide additional diagnostic and prognostic information beyond anatomic imaging alone 120. It is becoming increasingly evident that 18 F‐FDG PET/CT is capable of quantifying atherosclerotic inflammation and predicting subsequent cardiovascular events121 and providing a means of evaluating changes with treatment 122. Nevertheless, 18 F‐FDG lacks cell specificity, and in contrast to 18 F‐NaF, is extremely limited for the assessment of coronary arteries because of myocardial spillover in spite of significant efforts at background myocardial suppression 22…”
Section: Alternative Pet Imaging Tracersmentioning
confidence: 99%